2021
DOI: 10.3390/educsci11040181
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Digital Inequalities in Rural Schools in Germany: A Geographical Lottery?

Abstract: Repeatedly, it has been argued that advancements in digitalisation could be beneficial for rural areas. However, digital inequalities persist and affect rural communities as well. Schools can play a key role in bridging digital inequalities, but little attention has been paid to the specific conditions rural schools find themselves in when facing continuous digital developments. Therefore, we apply the digital inclusion lens and explore the impact of digital developments on rural schools in the German context.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 39 publications
2
19
0
3
Order By: Relevance
“…Regarding the variable of residential area, firstly, there is still a digital divide between rural and urban areas, resulting from demographic variables such as the age and education level of the population and the connection to the international internet [75,76]. The results in this study are consistent with [77], showing that digital competence is perceived to be on average better in university students living in urban areas.…”
Section: Discussionsupporting
confidence: 73%
“…Regarding the variable of residential area, firstly, there is still a digital divide between rural and urban areas, resulting from demographic variables such as the age and education level of the population and the connection to the international internet [75,76]. The results in this study are consistent with [77], showing that digital competence is perceived to be on average better in university students living in urban areas.…”
Section: Discussionsupporting
confidence: 73%
“…The municipality was found under pressure and probably also due to that, the future perspective tended to be neglected. Especially for smaller municipalities, it can be a challenge to keep constantly up to date with digital developments when they are already understaffed and underfunded (Rundel and Salemink, 2021). Thus, better support of municipalities to raise their capability to master digital adoption processes both within and beyond their organisational structure can be recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The reason is that phone screens are not conducive to long hours of digital online classes. Other studies affirmed that many rural students either don't have personal smartphones or they are available for a limited time (Rundel & Salemink, 2021;Padilla Rodriguez, 2021). Hence online learning during the fight against Covid-19 remains restricted to the limited availability of technological devices.…”
Section: Limited Availability Of Technological Devicesmentioning
confidence: 99%
“…On the contrary, some empirical investigation found that online education for urban students is more convenient and successful because their parents are financially stable to afford personal laptops and smartphones for their children. This makes online learning more interesting for township students (Sosa Díaz, 2021;Rundel & Salemink, 2021).…”
Section: Limited Availability Of Technological Devicesmentioning
confidence: 99%